The Law's Protection Against Children as Victims of Exploitation Artificial Intelligence-Based Cyberpornography - Sutarya, Idat Mustari; Prastiono, Suryo; Jamaludin, Ahmad (Journal of Law, Politic and Humanities, 2025)
Child sexual exploitation through AI-based cyberpornography is a serious and growing threat in the digital era. Advanced AI technologies, such as deepfake and AI bots, provide new opportunities for perpetrators to easily create and disseminate exploitative content, significantly impacting the physical, psychological, and social well-being of child victims. Although Indonesia has established legal frameworks such as the Child Protection Act and the Electronic Information and Transactions (ITE) Act, adaptive regulatory revisions and stronger implementation are needed to address AI-based crimes and provide maximum protection for children. This study aims to analyze the legal protection for children as victims of AI-based cyberpornography in Indonesia. It employs a normative juridical method focusing on the study of legal norms, both written and customary, to explore legal solutions to this issue. Using primary and secondary legal materials, the analysis is conducted descriptively and prescriptively to evaluate the application of existing laws and propose relevant enhancements or updates. The findings reveal that child sexual exploitation in AI-based cyberpornography represents a crime leveraging advanced technologies such as deepfake and AI chatbots, with serious psychological, social, and physical consequences for victims. Despite existing regulations such as the ITE Act and Child Protection Act, legal gaps related to AI use in these crimes demand regulatory reforms to address modern legal challenges and reinforce cross-sectoral collaboration